2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Emergency Planning and Community Right-to-Know [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Emergency planning and community right-to-know regulations facilitate awareness and emergency planning regarding the potential chemical hazards in local communities.  This is EDIS document FE395, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.